An Artemisia ordosica extract: Effects on growth performance, immune, and inflammatory response in lipopolysaccharide-challenged broilers - Shi, Lulu; Guo, Yanfei; Cheng, Yuchen; Xing, Yuanyuan; Guo, Shiwei; Zhang, Linghui; Xu, Yuanqing; Jin, Xiao; Yan, Sumei; Shi, Binlin (Frontiers in Veterinary Science, 2022)
Artemisia ordosica has been applied as a traditional Chinese/Mongolian medicine for treating certain inflammatory ailments. This study was conducted to investigate the effect of Artemisia ordosica alcohol extract (AOAE) supplemented in diets on growth performance, immune, and inflammatory response in lipopolysaccharide (LPS)-challenged broilers. A total of 240 one-day-old Arbor Acre male broilers were randomly allotted into 5 groups with 6 replicates (n = 8), which were basal diet group (CON), LPS-challenge and basal diet group (LPS), LPS-challenge and the basal diet added with low (500 mg/kg), middle (750 mg/kg), and high (1000 mg/kg) dose of AOAE groups (AOAE-L, AOAE-M, and AOAE-H), respectively. On d 16, 18, 20, 22, 24, 26, and 28, all broilers were injected intra-abdominally either with LPS or an equivalent amount of saline. Results showed that dietary AOAE alleviated the LPS-induced decrease in average daily gain and average daily feed intake in the broilers (P < 0.05). Dietary AOAE supplementation reversed the increased spleen index and the decreased bursa index in LPS-challenged broilers (P < 0.05). Moreover, feeding AOAE could mitigate the elevation of IL-1β in serum, liver, and spleen, IL-2 in serum and liver, IL-6 in serum and spleen, and the decrease of IgG in spleen, IgM in serum, liver, and spleen, and IL-4 in serum of the LPS-challenged broilers (P < 0.05). This study also showed that AOAE supplementation alleviated the increase of mRNA expression of TLR4, MyD88, TRAF6, NF-κB p65, NF-κB p50, IL-1β, and IL-6, and the decrease of gene expression of IκBα and PPARγ in liver and/or spleen of broilers challenged by LPS (P < 0.05). We speculated that AOAE administration could effectively alleviate LPS-induced inflammation via decreasing over-production of proinflammatory cytokines, ultimately relieving the growth inhibition of broilers caused by LPS. In conclusion, 1000 mg/kg AOAE has a strong capacity to enhance immunity and inhibit inflammation, and can be used as a potential novel feed additive with applications in treating inflammation-related diseases and bacterial infection in broilers.